Media Image of Chinese Youth: Fashionable Words in Microblogs of Weibo - Chuanya Ju; Yue Zheng; Yue Zhong (Научный диалог, 2023)
The question of the use of fashionable words as markers that contribute to the identification of social characteristics of various subjects of speech is considered. The material for the study was the texts of microblogs of the Weibo Internet platform dedicated to China. We study the use of 10 fashion words of 2021, identified by the National Center for Monitoring and Research of Language Resources. Their functioning on the Weibo Internet site is analyzed. It has been established that the majority of Weibo users belong to the younger generation. The relevance of the study is due to the desire of Chinese society to build a strong welfare state, in which a significant role is given to young people. The novelty of the work lies in the fact that earlier the analysis of fashionable words of the Chinese language in the Internet discourse as a means of characterizing the younger generation was not carried out. It is shown that fashionable words on Weibo in most cases are used in positive contexts, which can be considered as “achieving a stable development of the country”, since all microblogs are dedicated to China. The author comes to the conclusion that the topics of blogs and the nature of the use of fashionable words in youth accounts testify to the confidence of Chinese youth in their future and the future of the country.